Project management, planning, and control : managing engineering, construction, and manufacturing projects to PMI, APM, and BSI standards - Lester, Albert (Butterworth-Heinemann, 2014)
This book covers the principles and techniques needed to successfully manage an engineering or technical project from start to finish. Structured according to the logical sequence of a major project, with a strong focus on planning, scheduling, budgeting, and control, it focuses on the needs and challenges of project managers in engineering, manufacturing and construction, and closely aligned to the content of the APM and PMI 'bodies of knowledge'.